Laboratory manual for human biology - Morton, David; Perry, James W.; Perry, Joy B. 1952- (Belmont, California Brooks/Cole, 2012)
This lab manual includes inquiry-based experiments, relevant activities, and supporting questions that assess recall, understanding, and application. Each of the 21 exercises guides students through objectives, introduction, materials, procedure, pre-lab questions and post-lab questions.-- Source other than Library of Congress.
Learning about the natural world -- Observing microscopic details of the natural world -- Chemistry of life: biological molecules and diet analysis -- Cell structure -- Cell membranes and how they work -- Enzymes, the catalysts of life -- Homeostasis -- How mammals are constructed -- Support and movement: human skeletal and muscular systems -- External anatomy and organs of the digestive and respiratory systems -- Organs of the circulatory, urinary, and reproductive systems -- Human blood and circulation -- Human respiration -- Human sensations, reflexes, and reactions -- Structure and function of the sensory organs -- Reproduction and development -- Cell reproduction -- Human heredity -- DNA, genes, cancer, and biotechnology -- Evidences of evolution -- Human impact on the environment -- Measurement conversions -- Terms of orientation in and around animal body.
"Ideal for use in conjunction with Starr/McMillan's Human biology or any other human biology text"--Back cover.
Keywords: Human biology -- Laboratory manuals; Human biology